Aspirasi Pendidikan Orang Tua Dalam Mendukung Pendidikan Anak Di Asmat: Systematic Literature Review - Benediktus Rahawarin; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
This study aims to explore the educational aspirations of parents in Asmat Regency, South Papua, with respect to their support for their children's education, while considering the challenges posed by the nomadic lifestyle and complex geographical conditions. The research employs the Systematic Literature Review (SLR) method to analyze various literature concerning the relationship between parental aspirations and their efforts to enhance children's educational participation and achievement. The findings reveal that high parental educational aspirations significantly boost children's motivation to learn, their involvement in education, and academic performance. However, these aspirations are often hindered by external factors such as economic limitations, the influence of local cultural values, and inadequate educational infrastructure. The nomadic lifestyle and low literacy levels of parents further complicate the continuity of children's education. This study offers a unique perspective by focusing on the Asmat indigenous community, unlike previous studies that mostly focused on urban areas or regions with better educational access. The study recommends the development of inclusive educational policies, the implementation of literacy programs for parents, and improvements in infrastructure and community-based learning innovations to address educational barriers in Asmat. This research makes a valuable contribution to educational literature in remote areas and can serve as a foundation for creating more effective policies tailored to the needs of the local community.